2022
DOI: 10.3991/ijet.v17i18.32101
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Flipped Learning and Students’ Cognitive Engagement in Achieving Their Critical and Creative Thinking in Learning

Abstract: The 21st century as the information age implies that everyone, including students, must be literate in the development and advancement of knowledge-based information and communication technology. That is, students in schools as early as possible must be invited to build 21stcentury knowledge and skills, namely 4C skills. To accommodate this, the learning model must accommodate student centered learning models, one of which is quantum flipped learning (QFL) as a substitute for direct flipped learning (DFL). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…This finding can be concluded that the application of flipped learning has a positive influence on students' creative thinking abilities. The results of the study are in line with Agustini et al, (2022) The application of flipped learning has a significant effect on students' critical and creative thinking skills in learning. These results are also supported by research Suhartini &;Marianti (2023) said the application of flipped learning can have a positive influence on students' creative thinking and problem solving skills.…”
Section: Resultssupporting
confidence: 81%
“…This finding can be concluded that the application of flipped learning has a positive influence on students' creative thinking abilities. The results of the study are in line with Agustini et al, (2022) The application of flipped learning has a significant effect on students' critical and creative thinking skills in learning. These results are also supported by research Suhartini &;Marianti (2023) said the application of flipped learning can have a positive influence on students' creative thinking and problem solving skills.…”
Section: Resultssupporting
confidence: 81%
“…The visitor felt value could be determined by comparing what they give up (e.g., financial, time, power, and affection) with what they obtain (i.e., auratic experiences when looking at virtual objects). The satisfaction experienced by the visitor is obtained by quality of the museum experience, as well as the level of visitors fascinate, causes to overall museum visitors' satisfaction [88]. The opinion of visitors' satisfaction improves while the worth incorporation progression outcomes in a positive result are naturally more likely to foster positive effect.…”
Section: A Measurement Modelmentioning
confidence: 99%
“…Writing needs motivation among learners' to develop and enhance accuracy [67], [75]. Different strategies can be used to achieve this accuracy and fluency in writing [68], [76].…”
Section: Discussionmentioning
confidence: 99%